Low dielectric alkali soluble uv-polyimide resin, method of preparation and use thereof

CN122978348APending Publication Date: 2026-10-27ZHEJIANG TONGXIANG XIN ORIENT PRINTING INK CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611349462.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

仲羟基的存在显著增强了树脂整体的极性,导致固化膜的介电常数与介电损耗居高不下

Benefits of technology

[0022]综上所述,本发明通过单氨基单羧基氨基酸的定向闭环、含双键单环氧化合物的侧链接枝以及第二酸酐的羟基定向消除的协同作用,解决了高频印制电路板阻焊油墨中UV光固化、碱溶显影与极低介电性能互相制约的技术难题,提供了一种兼具低介电、高耐热、高附着力及优良工艺适应性的树脂与阻焊油墨体系。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978348A_ABST
    Figure CN122978348A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of polyimide resin, and particularly relates to a low-dielectric alkali-soluble UV polyimide resin, a preparation method and application thereof. The method comprises the following steps: S1: copolymerization of a monovinyl monomer and a first unsaturated acid anhydride to obtain an olefin copolymer with a side acid anhydride; S2: addition of a monoamino monocarboxyl amino acid for imidization reaction, ring closure of the amino group in the monoamino monocarboxyl amino acid and the side acid anhydride to form a maleimide ring, and retention of a free carboxyl group in the side chain; S3: addition of a single epoxy compound containing a double bond for ring-opening reaction with the free carboxyl group, introduction of a UV-curable double bond, and generation of a secondary hydroxyl group; and S4: addition of a second acid anhydride for esterification reaction with the secondary hydroxyl group to obtain the low-dielectric alkali-soluble UV polyimide resin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyimide resin technology, and particularly to a low dielectric alkali-soluble UV polyimide resin, its preparation method, and its application. Background Technology

[0002] With the rapid iteration of industries such as 5G communication, high-speed servers, cloud computing, high-frequency automotive electronics, and millimeter-wave radar, the signal transmission frequency and transmission rate of printed circuit boards are continuously increasing. Traditional solder resist inks are usually based on epoxy resin or ordinary acrylic resin, with a large number of polar groups in their molecular structure, resulting in high dielectric constant and dielectric loss. Under high-frequency operating conditions, these materials are prone to problems such as signal delay, signal attenuation, crosstalk interference, and severe heat generation, and can no longer meet the requirements of high-frequency and high-speed circuits.

[0003] Solder resist ink, as a core protective and insulating material on the surface of printed circuit boards, directly coats the circuitry and pads. Its dielectric properties have become a key factor restricting the transmission performance of high-frequency circuits, making low dielectric constant an inevitable development direction for high-end solder resist inks. However, in the synthesis of existing liquid photosensitive polyimides, a ring-opening reaction between a monoepoxide and a carboxyl group is typically used to introduce photosensitive double bonds. This process inevitably produces highly polar secondary hydroxyl groups. The presence of secondary hydroxyl groups significantly enhances the overall polarity of the resin, resulting in persistently high dielectric constant and dielectric loss in the cured film. Simultaneously, to ensure the alkaline solubility and developability of the solder resist ink, a certain amount of polar groups such as carboxyl groups must be retained. This creates a technical challenge where "UV curing," "alkaline solubility and developability," and "extremely low dielectric properties" in high-frequency printed circuit board solder resist inks often present mutually restrictive aspects. Therefore, how to minimize the density of polar groups while ensuring the resin possesses excellent photocuring activity and alkaline solubility and developability has become a critical problem urgently needing to be solved in this field. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a low-dielectric, alkali-soluble UV polyimide resin. The aim is to achieve UV curing and alkali-soluble development simultaneously through a four-step controllable synthesis process, thereby significantly reducing the dielectric constant and dielectric loss to meet the requirements of 5G and higher frequency communication circuit boards.

[0005] The technical solution adopted by this invention to solve its technical problem is:

[0006] A method for preparing a low-dielectric, alkali-soluble UV polyimide resin includes the following steps:

[0007] Step S1: The monovinyl monomer is copolymerized with the first unsaturated anhydride to obtain an olefin copolymer with a side anhydride. This step constructs the main chain backbone and provides uniformly distributed reaction sites for subsequent imidization reactions. A schematic diagram of the reaction is shown below. Figure 1 , where n, m = 1, 2, 3, 4...

[0008] Step S2: An imidization reaction is carried out by adding a monoamino-monocarboxylic amino acid. The amino group in the monoamino-monocarboxylic amino acid forms a maleimide ring with the side anhydride, while retaining a free carboxyl group in the side chain. By using a monoamino-monocarboxylic amino acid containing only one primary amino group and at least one carboxyl group instead of traditional aromatic or aliphatic diamines, a rigid maleimide ring can be formed while retaining a free carboxyl group in the side chain. This avoids the problems of excessive cross-linking of the main chain or the inability to directly retain the carboxyl group caused by traditional diamines containing two amino groups, thus simplifying the synthetic route and providing precise chemical sites for the subsequent introduction of UV-curing groups, achieving a synergistic effect of main chain rigidity and side chain functionalization. A schematic diagram of the reaction is shown below. Figure 2 .

[0009] Step S3: A monoepoxide compound containing a double bond is added to the free carboxyl group to undergo a ring-opening reaction, introducing a UV-curable double bond and simultaneously generating a secondary hydroxyl group. This step, through the ring-opening esterification reaction of the free carboxyl group and the epoxy group, grafts the photocurable double bond onto the side chain, endowing the resin with UV-responsive properties and enabling it to possess the photocurable capability required for photosensitive solder resist. A schematic diagram of the reaction is shown below. Figure 3 .

[0010] Step S4: Add a second acid anhydride to react with the secondary hydroxyl group in an esterification reaction, eliminating the secondary hydroxyl group and generating a reactive carboxyl group, thus obtaining the low-dielectric, alkali-soluble UV polyimide resin of the present invention. By setting this step, the highly polar secondary hydroxyl group generated in step S3 can be directionally eliminated using the second acid anhydride, converting the highly polar hydroxyl group into a low-polarity ester group, while simultaneously introducing a low-polarity saturated alicyclic structure and generating a new reactive carboxyl group. This reactive carboxyl group not only ensures the resin's solubility in alkaline developer, but also, because the hydroxyl group is completely eliminated, the density of polar groups after resin curing is extremely low, restricting molecular dipole motion, thereby significantly reducing the dielectric constant and dielectric loss, achieving a synergistic improvement in alkali-soluble development performance and low-dielectric performance. A schematic diagram of the reaction is shown below. Figure 4 .

[0011] In step S4, the amount of the second anhydride is stoichiometrically matched to the number of moles of the secondary hydroxyl groups generated in step S3, or slightly in excess, to ensure complete esterification. Each mole of secondary hydroxyl group undergoes esterification with one mole of anhydride, eliminating the strongly polar hydroxyl group while introducing an equimolar reactive carboxyl group for alkaline dissolution and development.

[0012] Preferably, in step S1, the monovinyl monomer is selected from at least one of vinyl styrene, α-methylstyrene, or methacrylate monomers, and the first unsaturated anhydride is selected from maleic anhydride or itaconic anhydride. By limiting these raw materials, it is possible to ensure that the free radical copolymerization reaction has suitable activity and conversion rate, forming a main chain structure with uniform side anhydride distribution.

[0013] Preferably, in step S2, the monoamino-carboxylic acid is selected from at least one of L-glycine, L-alanine, L-valine, L-leucine, L-isoleucine, L-proline, L-methionine, or L-phenylalanine. L-alanine and L-phenylalanine are preferred, in an amount of 0.98-1 moles of the acid anhydride, and the reaction temperature is 180-220°C. By selecting these natural amino acids, their well-defined monoamino structure allows for site-directed ring closure, while the presence of the carboxyl group provides a highly active site for subsequent ring-opening reactions, and their aliphatic side chains help further reduce overall polarity.

[0014] Preferably, in step S3, the monoepoxy compound containing double bonds is selected from at least one of glycidyl methacrylate (GMA), 3,4-epoxycyclohexyl methacrylate, or 3,4-epoxycyclohexyl acrylate. By introducing this type of epoxy acrylate containing an alicyclic or aliphatic backbone, the contribution of aromatic ring polarization can be reduced while introducing photocurable double bonds, which is beneficial for optimizing dielectric properties. 3,4-epoxycyclohexyl acrylate is preferred, with a molar ratio of 0.5-1 times that of the monoamino and monocarboxyl amino acids. Too few double bonds result in insufficient double bond content and inadequate sensitivity, while too many result in insufficient resin adhesion.

[0015] Preferably, in step S4, the second anhydride is selected from at least one inactive double-bond anhydride among phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride, or from at least one anhydride containing active double bonds among maleic anhydride or itaconic anhydride. Specifically, anhydrides with inactive double bonds, such as phthalic anhydride, tetrahydrophthalic anhydride, and hexahydrophthalic anhydride, provide the acid value to the resin structure; anhydrides containing active double bonds, such as maleic anhydride and itaconic anhydride, provide the acid value and unsaturated bonds to the resin. The reaction temperature is 100-110℃, the reaction time is 2 hours, and the addition amount is to maintain the resin acid value at 50-150 mg KOH / g; the double bond equivalent is 200-2000 g / eq. Through this selection design, when using anhydrides with inactive double bonds, the focus can be on reducing polarity and providing alkali-soluble carboxyl groups; when using anhydrides containing active double bonds, the double bond density of the resin can be further increased while eliminating secondary hydroxyl groups, thereby improving the UV curing crosslinking density without adding additional photocurable monomers, achieving a balance between dielectric properties and curing properties.

[0016] Preferably, based on the total weight parts of the raw materials, the monovinyl monomer is 1 to 20 parts, and the first unsaturated anhydride is 10 to 30 parts; in step S2, the monoamino-monocarboxylic amino acid is 8 to 20 parts; in step S3, the monoepoxide compound containing double bonds is 8 to 40 parts; and in step S4, the second anhydride is 10 to 30 parts. This ratio range ensures that the functional group equivalents are matched in each step, allowing the copolymer backbone, closed-ring imide, UV double bond ring-opening, and end-capping esterification reactions to proceed fully, avoiding raw material residue or insufficient crosslinking, thereby balancing the resin's storage stability, development resolution, and cured film density.

[0017] More preferably, in steps S1 to S4, based on the total weight parts of the raw materials, the monovinyl monomer is 3 to 15 parts, the first unsaturated anhydride is 12 to 15 parts, the monoamino monocarboxyl amino acid is 9 to 12 parts, the monoepoxide compound containing double bonds is 9 to 20 parts, and the second anhydride is 11 to 16 parts.

[0018] Optionally, steps S1 to S4, based on the total weight parts of the raw materials, further include reaction aids, specifically: 30 to 40 parts solvent, 0.50 to 2.50 parts initiator, 0.05 to 0.25 parts catalyst, and 0.01 to 1.0 parts polymerization inhibitor. Specifically, the copolymerization reaction in step S1 is carried out in a solvent with the addition of an appropriate amount of initiator; in step S3, an appropriate amount of catalyst and polymerization inhibitor are added to carry out a ring-opening reaction. The solvent is selected from diethylene glycol ethyl ether acetate, γ-butyrolactone; the catalyst is selected from triphenylphosphine, 4-dimethylaminopyridine, 2,4,6-tris(dimethylaminomethyl)phenol, etc.; the polymerization inhibitor is selected from p-hydroxyanisole, hydroquinone, 2,6-di-tert-butyl-p-cresol, etc. The initiator is a commonly used initiator in the art for free radical copolymerization reactions, including but not limited to benzoyl peroxide, tert-butyl hydroperoxide, azobisisobutyronitrile, etc. Its dosage is 0.50 to 2.50 parts based on the total weight of the raw materials, and is matched with the copolymerization reaction temperature of 90°C to 130°C, so as to effectively initiate the copolymerization of the monovinyl monomer and the first unsaturated anhydride.

[0019] Preferably, in step S1, the copolymerization reaction temperature is 90℃ to 130℃, and the reaction time is 4-8 hours; in step S2, a water separator is used for dehydration, and the imidization reaction temperature is 180℃ to 220℃, with a reaction time of 6-9 hours; in step S3, the ring-opening reaction temperature is 90℃ to 120℃, and the reaction time is 6-8 hours; in step S4, the esterification reaction temperature is 100℃ to 110℃, and the reaction time is 1-3 hours. This temperature control ensures stable free radical copolymerization in step S1, suppressing chain transfer and side reactions; the high-temperature dehydration in step S2 promotes ring closure and the formation of a stable maleimide ring; the medium-temperature ring-opening in step S3 achieves high conversion rates while avoiding double-bond thermal polymerization; and the mild esterification in step S4 effectively suppresses the side reactions of secondary hydroxyl groups, ensuring end-capping efficiency and maximizing the elimination of polar hydroxyl groups.

[0020] A low-dielectric, alkali-soluble UV-curable polyimide resin is prepared using any of the methods described above. Because the secondary hydroxyl groups are completely eliminated through anhydride esterification during the four-step synthesis process, and a low-polarity saturated alicyclic structure is embedded in the main chain, this resin exhibits significantly low polar group density and restricted molecular dipole motion. After curing, under 10GHz testing conditions, the dielectric constant is as low as 2.50–3.10, and the dielectric loss is as low as 0.0007–0.0018.

[0021] A photosensitive solder resist ink composition comprises the aforementioned low-dielectric alkali-soluble UV polyimide resin. In a preferred embodiment, the photosensitive solder resist ink composition further comprises a photoinitiator, an amine synergist, a filler, and a low-dielectric epoxy resin. By introducing the photoinitiator and amine synergist into the composition, UV free radical polymerization of unsaturated double bonds in the resin can be efficiently initiated; by introducing the low-dielectric epoxy resin, a double crosslinking network can be formed with the resin during the thermosetting stage, improving the density, heat resistance, and chemical resistance of the cured film. In a more preferred embodiment, by weight, the photosensitive solder resist ink composition comprises 50 parts of the aforementioned low-dielectric alkali-soluble UV polyimide resin, 10 parts of polymeric monomer, 6 parts of photoinitiator, 1 part of amine synergist, 10 parts of barium sulfate, and 20 parts of dicyclopentadiene epoxy resin. This precise formulation enables the construction of a dual crosslinking system that combines UV curing and epoxy thermosetting, resulting in a solder resist layer with extremely low dielectric constant and dielectric loss, as well as high copper foil adhesion, excellent high-temperature solder resistance, and chemical gold resistance.

[0022] In summary, this invention solves the technical challenge of mutual constraints between UV curing, alkali-soluble development, and extremely low dielectric properties in high-frequency printed circuit board solder resist inks through the synergistic effect of directional ring closure of monoamino and monocarboxylic amino acids, side linking of double-bonded monoepoxide compounds, and directional elimination of hydroxyl groups in the second anhydride. It provides a resin and solder resist ink system that combines low dielectric, high heat resistance, high adhesion, and excellent process adaptability. Attached Figure Description

[0023] Figure 1 This is a schematic diagram of the reaction in step S1 of the preparation method of the low dielectric alkali-soluble UV polyimide resin of the present invention.

[0024] Figure 2 This is a schematic diagram of step S2 in the preparation method of the low dielectric alkali-soluble UV polyimide resin of the present invention.

[0025] Figure 3 This is a schematic diagram of the reaction in step S3 of the preparation method of the low dielectric alkali-soluble UV polyimide resin of the present invention.

[0026] Figure 4 This is a schematic diagram of the reaction in step S4 of the preparation method of the low dielectric alkali-soluble UV polyimide resin of the present invention.

[0027] Figure 5 This is the infrared characterization spectrum of the low dielectric alkali-soluble UV polyimide resin prepared in Example 1 of the present invention. Detailed Implementation

[0028] The technical solution of the present invention will be further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any modifications and / or alterations made to the present invention will fall within the protection scope of the present invention.

[0029] In this invention, unless otherwise specified, all parts and percentages are by weight, and the equipment and raw materials used are commercially available or commonly used in the art. Unless otherwise specified, the methods in the following embodiments are conventional methods in the art.

[0030] Unless otherwise specified, the reagents used in the following examples can be purchased from a regular biochemical reagent store.

[0031] Source of raw materials:

[0032] γ-Butyrolactone, Shandong Zhouhe Chemical Co., Ltd.;

[0033] Styrene, China Petroleum & Chemical Corporation;

[0034] Maleic anhydride, Zibo Qixiang Tengda Chemical Co., Ltd., China;

[0035] Glycine, alanine, Hebei Chuangzhiyuan Biotechnology Co., Ltd.;

[0036] 3,4-Epoxycyclohexyl acrylate, ATT16, Jiangsu Taitel New Material Technology Co., Ltd.;

[0037] GMA, Shandong Guangpu Biotechnology Co., Ltd.

[0038] Hexahydrophthalic anhydride, Puyang Huicheng Electronic Materials Co., Ltd.;

[0039] Dipentaerythritol hexaacrylate, Jiangsu Kailin Ruiyang Chemical Co., Ltd.;

[0040] Photoinitiators 2-isopropylthioxanthone (ITX), 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone (907), ethyl 4-dimethylaminobenzoate (EDB), Jiuri Chemical;

[0041] Barium sulfate, Jiaen Chemical (Shandong) Co., Ltd.;

[0042] Dicyclopentadiene epoxy resin, SQDN-302, Shandong Shengquan Group Co., Ltd.;

[0043] Defoamer, model KS-66, Shin-Etsu Chemical;

[0044] Leveling agent, model BKY-354, BYK Chemicals, Germany.

[0045] Example 1

[0046] A low-dielectric, alkali-soluble UV polyimide resin has the following raw material composition by weight: 40 parts γ-butyrolactone, 3.29 parts styrene, 12.40 parts maleic anhydride, 9.49 parts glycine, 19.23 parts 3,4-epoxycyclohexyl acrylate, 15.59 parts hexahydrophthalic anhydride, 1.50 parts azobisisobutyronitrile, 0.10 parts triphenylphosphine, and 0.20 parts p-hydroxyanisole.

[0047] The polyimide resin in this embodiment is prepared through the following steps:

[0048] 1. Add γ-butyrolactone to a stirred reactor, start stirring, and heat to 90℃~130℃, maintaining a constant temperature. Thoroughly mix styrene (monomer), maleic anhydride, and azobisisobutyronitrile, then add the mixture dropwise to the reactor over 5 hours. After the addition is complete, maintain the temperature to allow the reaction to proceed, yielding an olefin copolymer with a lateral anhydride.

[0049] 2. Subsequently, glycine was added to the reaction vessel and the temperature was gradually raised to 200°C. The reaction was maintained at this temperature for about 8 hours. During the reaction, a water separator was used to continuously dehydrate the glycine, so that the amino group in the glycine and the side anhydride closed the ring to form a maleimide ring, while retaining a free carboxyl group in the side chain.

[0050] 3. After the reaction solution cools to 90℃~120℃, add 3,4-epoxycyclohexyl acrylate, triphenylphosphine (catalyst) and p-hydroxyanisole (polymerization inhibitor), and keep the reaction in air for about 8 hours to open the ring of free carboxyl groups and epoxy groups, introduce UV-curable double bonds, and generate secondary hydroxyl groups at the same time.

[0051] 4. Finally, hexahydrophthalic anhydride is added, and the mixture is kept at 100℃~110℃ for about 2 hours to allow the hexahydrophthalic anhydride to undergo an esterification reaction with the aforementioned secondary hydroxyl groups, eliminating the secondary hydroxyl groups and generating reactive carboxyl groups, thus obtaining a low-dielectric, alkali-soluble UV polyimide resin. The resin has an unsaturated equivalent of 592 g / eq and a solid acid value of 118 mg KOH / g.

[0052] like Figure 5 As shown, the low-dielectric, alkali-soluble UV polyimide resin prepared in Example 1 was subjected to infrared spectroscopy. The figure shows that the resin exhibits good performance at a wavenumber of approximately 3006 cm⁻¹. -1 A broad and strong absorption peak appears at approximately 1776 cm⁻¹, attributed to the stretching vibration of the OH bond in the carboxyl group. This indicates that the carboxyl group of the amino acid in step S2 is retained, and that the reactive carboxyl group newly generated after the esterification of the second anhydride with the secondary hydroxyl group in step S4 exists in the resin molecule structure. -1 The presence of a characteristic absorption peak at approximately 1636 cm⁻¹ at a wavenumber of approximately 1636 cm⁻¹ indicates that the amino group of glycine and the lateral anhydride in step S2 have successfully formed a maleimide ring, and the polyimide backbone structure has been completed. -1 The presence of a moderate absorption peak at this point is attributed to the stretching vibration of the C=C double bond in acrylates, proving that the monoepoxide compound containing the double bond in step S3 has successfully undergone a ring-opening reaction with the free carboxyl group on the side chain, and that a UV-curable reactive double bond has been introduced into the resin molecule.

[0053] Crucially, at a wavenumber of 3200 cm⁻¹ -1 Up to 3600 cm -1 Within the specified range, apart from the broad peak at the carboxyl group mentioned above, no significant independent absorption peaks attributed to the secondary hydroxyl group were observed. This phenomenon indicates that the secondary hydroxyl group generated in the ring-opening reaction of step S3 was completely eliminated by the second acid anhydride in step S4, and the strongly polar hydroxyl group was converted into a low-polarity ester group. Meanwhile, at a wavenumber of approximately 1100 cm⁻¹... -1 The strong absorption peaks that appear nearby are attributed to the stretching vibration of the COC bond in the ester group, which further corroborates the occurrence of the esterification reaction from another perspective.

[0054] The aforementioned infrared spectral characteristics confirm the successful implementation of the four-step synthetic route of this invention at the molecular structure level: the polyimide ring and UV-curable double bond coexist in the resin backbone, while reactive carboxyl groups are retained and secondary hydroxyl groups are completely eliminated in the side chains. This molecular structure of "carboxyl group retention and hydroxyl group elimination" allows the resin to have the carboxyl groups required for alkali solubility and development while minimizing the density of polar groups.

[0055] Example 2

[0056] A low-dielectric, alkali-soluble UV polyimide resin has the following raw material composition by weight: 40 parts γ-butyrolactone, 13.24 parts styrene, 12.47 parts maleic anhydride, 9.55 parts alanine, 9.06 parts 3,4-epoxycyclohexyl acrylate, 15.68 parts hexahydrophthalic anhydride, 1.50 parts azobisisobutyronitrile, 0.10 parts triphenylphosphine, and 0.20 parts p-hydroxyanisole.

[0057] The preparation steps of the polyimide resin in this embodiment are basically the same as those in Example 1, with the main difference being the different proportions of each raw material and the substitution of alanine for glycine. Specifically, γ-butyrolactone is added to a stirred reactor, stirring is started, and the temperature is raised to 90℃~130℃ and maintained at a constant temperature. Styrene, maleic anhydride, and azobisisobutyronitrile are mixed and added dropwise to the reactor over a period of 5 hours. Then, alanine is added to the reactor, and the temperature is gradually raised to about 200℃ and maintained for 8 hours, with dehydration using a water separator during the reaction. After cooling to 90℃~120℃, 3,4-epoxycyclohexyl acrylate, triphenylphosphine, and p-hydroxyanisole are added, and the mixture is kept at an air temperature for 8 hours. Finally, hexahydrophthalic anhydride is added, and the mixture is kept at 100℃~110℃ for 2 hours to obtain the target resin. The unsaturated equivalent of this resin is 589 g / eq, and the solid acid value is 119 mg KOH / g.

[0058] Example 3

[0059] A low-dielectric alkali-soluble UV polyimide resin has the following raw material composition by weight: 40 parts γ-butyrolactone, 12.83 parts styrene, 12.09 parts maleic anhydride, 9.25 parts glycine, 12.52 parts glycidyl methacrylate, 13.308 parts hexahydrophthalic anhydride, 1.50 parts azobisisobutyronitrile, 0.10 parts triphenylphosphine, and 0.20 parts p-hydroxyanisole.

[0060] The preparation steps of the polyimide resin in this embodiment are basically the same as those in Example 1, except that glycidyl methacrylate is used as a monoepoxide compound containing double bonds in step S3. Specifically, γ-butyrolactone is added to a stirred reactor, stirring is started, and the temperature is raised to 90℃~130℃ and maintained at a constant temperature. Styrene, maleic anhydride, and azobisisobutyronitrile are mixed and added dropwise to the reactor over a period of 5 hours. Glycine is then added to the reactor, and the temperature is gradually raised to about 200℃ and maintained for 8 hours, with dehydration using a water separator during the reaction. After cooling to 90℃~120℃, glycidyl methacrylate, triphenylphosphine, and p-hydroxyanisole are added, and the mixture is kept at a constant temperature in air for 8 hours. Finally, hexahydrophthalic anhydride is added, and the mixture is kept at 100℃~110℃ for 2 hours to obtain the target resin. The unsaturated equivalent of this resin is 695 g / eq, and the solid acid value is 115 mg KOH / g.

[0061] Comparative Example 1

[0062] This comparative example uses the traditional epoxy acrylic route to prepare solder resist resin, which contains the following raw materials in parts by weight: 40 parts diethylene glycol ethyl ether acetate, 14 parts o-cresol epoxy resin, 5 parts acrylic acid, 9 parts tetrahydrophthalic anhydride, 0.2 parts triphenylphosphine, and 0.5 parts hydroquinone.

[0063] The resin preparation steps for this comparative example are as follows: Diethylene glycol ethyl ether acetate was added to a stirred reactor, stirring was started, and the temperature was raised to 90℃~110℃. o-Cresol epoxy resin was then added and dissolved. Subsequently, the reaction solution temperature was set at 110℃, and acrylic acid (monomer), triphenylphosphine, and hydroquinone were added. The reaction was maintained at 110℃ in air for 10 hours. Then, tetrahydrophthalic anhydride was added, and the reaction was maintained at 105℃ for 2 hours, thus obtaining the traditional liquid photosensitive solder resist resin.

[0064] Comparative Example 2

[0065] An alkali-soluble UV polyimide resin has the following raw material composition by weight: 40 parts γ-butyrolactone, 3.83 parts styrene, 14.43 parts maleic anhydride, 11.04 parts glycine, 19.58 parts 3,4-epoxycyclohexyl acrylate, 11.11 parts hexahydrophthalic anhydride, 1.50 parts azobisisobutyronitrile, 0.10 parts triphenylphosphine, and 0.20 parts p-hydroxyanisole.

[0066] The preparation steps of the polyimide resin in this embodiment are basically the same as those in Example 1. The difference lies in step S4, where the hydroxyl groups generated in step S3 are not completely acidified, and the secondary hydroxyl groups generated in step S3 are not completely esterified and eliminated, resulting in residual secondary hydroxyl groups in the resin. Specifically, γ-butyrolactone is added to a stirred reactor, stirring is started, and the temperature is raised to 90℃~130℃ and maintained at a constant temperature. Styrene, maleic anhydride, and azobisisobutyronitrile are mixed and added dropwise to the reactor over a period of 5 hours. Glycine is then added to the reactor, and the temperature is gradually raised to about 200℃ and maintained for 8 hours, with dehydration using a water separator during the reaction. After cooling to 90℃~120℃, glycidyl methacrylate, triphenylphosphine, and p-hydroxyanisole are added, and the mixture is kept at air for 8 hours. Finally, hexahydrophthalic anhydride is added, and the mixture is kept at 100℃~110℃ for 2 hours to obtain the target resin. The resin has an unsaturated equivalent of 582 g / eq and a solid acid value of 109 mg KOH / g.

[0067] In Comparative Example 2, the amount of hexahydrophthalic anhydride used was 11.11 parts, which was significantly less than the 15.59 parts used in Example 1. As a result, the secondary hydroxyl groups generated in step S3 were not completely esterified, and some strongly polar hydroxyl groups remained in the resin.

[0068] Performance testing

[0069] The low-dielectric alkali-soluble UV polyimide resins obtained in Examples 1-3 and the conventional resin obtained in Comparative Example 1 were formulated into photosensitive solder resist ink compositions according to the formulations shown in Table 1, and their performance was tested. All raw material amounts in Table 1 are parts by weight.

[0070] Table 1

[0071]

[0072] The testing steps are as follows:

[0073] (1) Coating: The above composition is coated onto the printed circuit board substrate by screen printing, so that the thickness of the dry film is 15 micrometers to 25 micrometers.

[0074] (2) Pre-drying: Dry with a hot air dryer at 75℃ for 30 minutes.

[0075] (3) Exposure and development: Ultraviolet light is irradiated through the film on which the circuit diagram is drawn using an ultraviolet exposure device. Then, a 1% sodium carbonate aqueous solution is used for spray development to remove the resin in the parts not exposed to ultraviolet light, followed by washing and drying.

[0076] (4) Post-curing: Heat the printed substrate for 60 minutes using a hot air dryer at 150°C.

[0077] The cured products were tested for pre-baking tack, developability, resolution, cured adhesion, solderability, chemical gold resistance, dielectric constant of the solder resist layer, and dielectric loss. The dielectric constant and dielectric loss were measured at 10 GHz. The test results of each example and comparative example are shown in Table 2.

[0078] Table 2

[0079]

[0080] The performance evaluation method is as follows:

[0081] (1) Pre-baking tack: The coating layer was dried in a hot air dryer at 75°C for 30 minutes, and then vigorously wiped on the dried film coated on the substrate with degreased cotton to evaluate it.

[0082] ○ – Non-adhesive; × – Adhesive

[0083] (2) Developability: The residue on the copper foil after the pre-dried coating is exposed and developed.

[0084] ○ — No residue; × — Residue present

[0085] (3) Resolution: After development, the resolution of different line widths and line spacings is confirmed based on the exposed pattern.

[0086] (4) Adhesion after curing—GB / T 1720–79(89).

[0087] ○ – Not detached; × – Detached

[0088] (5) Solder resistance—Apply rosin-based flux to the surface of the coating and immerse it in a lead-tin furnace at 288°C for 30 seconds; wipe the surface with ethylene glycol butyl ether and tear off 3M tape (model 610#) three times.

[0089] ○ – Not detached; × – Detached.

[0090] (6) Gold resistance: Gold is applied using gold-repellent solution. After gold treatment, 3M tape (model 610#) is used to peel the surface three times and the following criteria are used for evaluation.

[0091] ○ — Not dropped; × — Dropped.

[0092] According to the test results in Table 1:

[0093] From the dielectric performance data, compared with Comparative Example 1, Examples 1, 2, and 3 all showed significantly superior dielectric constants and dielectric losses under 10GHz high-frequency conditions. The dielectric constant of the solder resist layer in Comparative Example 1 was as high as 3.80, and the dielectric loss was as high as 0.0025, while the dielectric constant of Example 1 decreased to 2.50, and the dielectric loss decreased to 0.0007, representing reductions of approximately 34% and 72%, respectively. Comparative Example 1 used a conventional ring-opening reaction between o-cresol epoxy resin and acrylic acid. Although this process introduced photocurable double bonds, it also retained a large number of secondary hydroxyl groups on the molecular side chains. Furthermore, the end-capping of tetrahydrophthalic anhydride did not directionally eliminate these hydroxyl groups, resulting in an extremely high density of polar groups in the cured resin molecules. Under the action of a high-frequency electric field, the hydroxyl groups and residual carboxyl groups underwent strong dipole orientation polarization, leading to active molecular dipole motion and a significant increase in energy loss, thus exhibiting higher dielectric constants and dielectric losses. Example 1 employed a four-step controllable synthesis route. In step S2, the primary amino group of glycine, a monoamino-carboxylic acid, is used to form a maleimide ring with the side anhydride. This rigid ring structure effectively restricts the movement of the main chain molecular segments and reduces the dipole turning ability at low frequencies, thus laying the structural foundation for reducing dielectric loss. Simultaneously, since glycine contains only one primary amino group, the side chain retains a free carboxyl group after the reaction. This carboxyl group not only eliminates the need for introducing other polar carboxyl sources but also provides a site for precise ring-opening in step S3. In step S3, the monoepoxide compound 3,4-epoxycyclohexyl acrylate containing a double bond undergoes ring-opening with the free carboxyl group, introducing a UV-curable double bond. This is a necessary step for photolithographic patterning, but it inevitably generates a secondary hydroxyl group. Step S4 is the core step in achieving a breakthrough in dielectric performance in this invention: hexahydrophthalic anhydride is added as a second anhydride to undergo an esterification reaction with the secondary hydroxyl group generated in step S3. This reaction completely converts the highly polar secondary hydroxyl group into a low-polarity ester group. Simultaneously, the saturated alicyclic structure of hexahydrophthalic anhydride is introduced into the molecular side chain, significantly reducing the molecular polarizability and dipole moment. More importantly, this esterification reaction also generates a new reactive carboxyl group, which is precisely used to ensure the resin's solubility in alkaline developing solutions. Thus, without adding additional polar groups, both alkaline developing performance and low dielectric properties are achieved.

[0094] Example 2 uses the same four-step process and hexahydrophthalic anhydride end-capping as Example 1, but the proportions of each raw material are adjusted. In Example 2, the amount of the monovinyl monomer styrene is reduced, while the amount of the monoepoxide compound containing double bonds is increased, resulting in a decrease in the unsaturated equivalent of the resin to 589 eq / g and an increase in the double bond density. After curing, the dielectric constant was tested to be 2.70 and the dielectric loss was 0.0010, which is still far superior to Comparative Example 1. This indicates that, provided that the secondary hydroxyl group is fully eliminated by the second anhydride in step S4, the overall low polarity framework of the molecule is maintained, and the dielectric properties have a good tolerance to fluctuations in double bond density. It also proves that the raw material proportions in steps S1 to S4 can achieve the low dielectric target within a wide range.

[0095] In Example 3, the monoepoxide compound containing double bonds was replaced with glycidyl methacrylate. Compared to the alicyclic epoxy structure of Example 1, glycidyl methacrylate has an aliphatic linear structure, and its molecular backbone polarizability is slightly higher than that of the alicyclic structure. Therefore, the dielectric constant of Example 3 is 3.10, and the dielectric loss is 0.0018, which is slightly higher than that of Example 1, but still significantly lower than that of Comparative Example 1. This comparison further illustrates that the elimination of secondary hydroxyl groups by the second anhydride is the primary factor in reducing dielectric loss, and the use of alicyclic structures in the monoepoxide compound containing double bonds can further optimize the dielectric properties.

[0096] In terms of resolution, Examples 1 and 2 both achieved 25 micrometers, which is superior to the 50 micrometers achieved by Examples 3 and Comparative Examples 1 and 2. The reason for this is that the 3,4-epoxycyclohexyl acrylate used in Examples 1 and 2 has a rigid alicyclic skeleton, and the steric hindrance of the side chains formed after ring opening is relatively large, which helps to improve the edge sharpness of the double bond crosslinked region after exposure, thereby improving the development resolution. However, the glycidyl methacrylate chain in Example 3 has higher flexibility, and the boundary uniformity of the crosslinked region after exposure is relatively weaker, resulting in a slight decrease in resolution. Nevertheless, the 50-micrometer resolution of Example 3 still meets the requirements of conventional solder resist processes.

[0097] Regarding resistance to chemically treated gold, Examples 1-3 all exhibited excellent performance, while Comparative Examples 1 and 2 showed detachment. This difference fully demonstrates the superiority of the polyimide backbone structure of the present invention. The traditional epoxy acrylic system of Comparative Example 1 lacks a rigid imide ring structure. Under prolonged exposure to chemically treated gold solutions, the molecular network is prone to swelling or penetration, leading to adhesion failure. In contrast, the embodiments of the present invention incorporate maleimide rings embedded in the backbone. This ring structure possesses excellent chemical stability and rigidity. Furthermore, the dual crosslinking network formed by UV-cured double bonds and thermosetting dicyclopentadiene epoxy resin results in a cured film with extremely high crosslinking density and chemical resistance, effectively resisting the attack of chemically treated gold solutions and exhibiting excellent resistance to chemically treated gold.

[0098] Comparative data from Example 1 and Comparative Example 2 demonstrate that the amount of the second anhydride and the degree of elimination of secondary hydroxyl groups in step S4 are key control points for regulating dielectric properties. Even with a low-polarity polyimide backbone, if the secondary hydroxyl groups are not completely eliminated through esterification with the second anhydride, the dielectric loss of the resin will rapidly rise back to the level of traditional epoxy acrylic systems, and the dielectric constant will also deteriorate significantly. Only through sufficient feeding of the second anhydride and complete esterification can the strongly polar hydroxyl groups be completely converted into low-polarity ester groups while retaining the alkali-soluble reactive carboxyl groups, thereby achieving a true balance between low dielectric strength and developing performance.

[0099] Furthermore, all embodiments performed satisfactorily in terms of pre-baking tack, developability, cured adhesion, and solder resistance, showing comparable to or better than Comparative Example 1. This demonstrates that while significantly reducing dielectric constant and dielectric loss, the present invention has not sacrificed the basic process performance and reliability of the solder resist ink. On the contrary, through the rational design of the molecular structure, a balance between low dielectric properties and overall performance has been achieved.

[0100] In summary, this invention constructs a low-dielectric, alkali-soluble UV polyimide resin with extremely low polar group density and restricted molecular dipole motion through the synergistic effect of three core steps: directional imidization ring closure of monoamino and monocarboxylic amino acids, side linking with double-bonded monoepoxide compounds, and directional esterification elimination of secondary hydroxyl groups by a second acid anhydride. When this resin is compounded with photoinitiators, amine synergists, and low-dielectric epoxy resins, a dual crosslinking system of UV curing and thermosetting is formed. This system exhibits unexpectedly low dielectric constant and low dielectric loss at 10 GHz, while also possessing high resolution, high adhesion, solder resistance, and excellent anti-metal properties, providing a reliable material solution for solder resist inks used in 5G high-frequency and high-speed circuit boards.

[0101] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a low-dielectric, alkali-soluble UV polyimide resin, characterized in that, The method includes the following steps: Step S1: The monovinyl monomer is copolymerized with the first unsaturated anhydride to obtain an olefin copolymer with a side anhydride; Step S2: Add a monoamino monocarboxylic acid to carry out an imidization reaction, using the amino group in the monoamino monocarboxylic acid to form a maleimide ring with the side anhydride, and retaining a free carboxyl group in the side chain; Step S3: Add a monoepoxide compound containing a double bond to the free carboxyl group to carry out a ring-opening reaction, introduce a UV-curable double bond, and generate a secondary hydroxyl group at the same time; Step S4: Add the second acid anhydride and the secondary hydroxyl group to carry out an esterification reaction to obtain a low dielectric alkali-soluble UV polyimide resin.

2. The preparation method according to claim 1, characterized in that, In step S1, the monovinyl monomer is selected from at least one of vinyl styrene, α-methylstyrene, or (meth)acrylate monomers, and the first unsaturated anhydride is selected from maleic anhydride or itaconic anhydride; in step S2, the monoamino monocarboxylic amino acid is selected from at least one of L-glycine, L-alanine, L-valine, L-leucine, L-isoleucine, L-proline, L-methionine, or L-phenylalanine.

3. The preparation method according to claim 1, characterized in that, In step S3, the monoepoxide compound containing double bonds is selected from at least one of glycidyl methacrylate, 3,4-epoxycyclohexyl methacrylate, or 3,4-epoxycyclohexyl acrylate; in step S4, the second anhydride is selected from at least one inactive double-bonded anhydride selected from phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride, or from at least one active double-bonded anhydride selected from maleic anhydride or itaconic anhydride.

4. The preparation method according to claim 1, characterized in that, In steps S1 to S4, based on the total weight parts of the raw materials, The monovinyl monomer is present in amounts of 1 to 20 parts. The first unsaturated acid anhydride is 10 to 30 parts. The monoamino monocarboxylic acid is present in amounts of 8 to 20 parts. The monoepoxide compound containing double bonds is present in amounts of 8 to 40 parts. The second acid anhydride is 10 to 30 parts.

5. The preparation method according to claim 1, characterized in that, In steps S1 to S4, based on the total weight parts of the raw materials, reaction aids are also included, specifically: 30 to 40 parts of solvent, 0.50 to 2.50 parts of initiator, 0.05 to 0.25 parts of catalyst, and 0.01 to 1.0 parts of polymerization inhibitor.

6. The preparation method according to claim 1, characterized in that, In step S1, the copolymerization reaction is carried out at a temperature of 90°C to 130°C for 4-8 hours. In step S2, a water separator is used for dehydration, the temperature of the imidization reaction is 180°C to 220°C, and the reaction time is 6-9 hours. In step S3, the ring-opening reaction is carried out at a temperature of 90°C to 120°C for 6-8 hours. In step S4, the esterification reaction temperature is 100°C to 110°C, and the reaction time is 1-3 hours.

7. A low-dielectric, alkali-soluble UV-cured polyimide resin, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 5.

8. A photosensitive solder resist ink composition, characterized in that, It comprises the low dielectric alkali-soluble UV polyimide resin as described in claim 6.

9. The photosensitive solder resist ink composition according to claim 8, characterized in that, It also includes photoinitiators, amine synergists, fillers, and low-dielectric epoxy resins.

10. The photosensitive solder resist ink composition according to claim 9, characterized in that, By weight, the photosensitive solder resist ink composition comprises 50 parts of the low dielectric alkali-soluble UV polyimide resin, 10 parts of polymeric monomer, 6 parts of photoinitiator, 1 part of amine synergist, 10 parts of barium sulfate, and 20 parts of dicyclopentadiene epoxy resin.